2009
DOI: 10.5641/027013609x13087704027751
|View full text |Cite
|
Sign up to set email alerts
|

Preadolescent Female Development Through Sport and Physical Activity: A Case Study of an Urban After-School Program

Abstract: Youth development research has found that children become more engaged and benefit more from being incorporated as decision makers. Thus participation helps promote development and encourages engagement. Based in theories of engagement and free-choice learning, the current research focused on a program combining sport/physical activity, life skills, and mentoring while promoting healthy life choices for preadolescent girls of color The co-investigators, all women, conducted two 2-hr visits per week for two 12-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
0
11
0
3
Order By: Relevance
“…Ullrich-French et al, who reported a growth, operationalized social competence in a way that overlaps with social interaction skills, whereas Laberge et al, who did not report a growth, operationalized social competence in a way that overlaps with social responsibility skills (i.e., respecting others and being polite). The findings from the work by Bruening et al (2009), who conducted a qualitative case study, were less positive. Although the researchers reported a growth in prosocial involvement in African American and Latina girls who participated in weekly sports sessions and life skills sessions, they only provided a few examples of improvements in behavioral competencies (Bruening et al, 2009).…”
Section: Social Life Skillsmentioning
confidence: 95%
See 1 more Smart Citation
“…Ullrich-French et al, who reported a growth, operationalized social competence in a way that overlaps with social interaction skills, whereas Laberge et al, who did not report a growth, operationalized social competence in a way that overlaps with social responsibility skills (i.e., respecting others and being polite). The findings from the work by Bruening et al (2009), who conducted a qualitative case study, were less positive. Although the researchers reported a growth in prosocial involvement in African American and Latina girls who participated in weekly sports sessions and life skills sessions, they only provided a few examples of improvements in behavioral competencies (Bruening et al, 2009).…”
Section: Social Life Skillsmentioning
confidence: 95%
“…The findings from the work by Bruening et al (2009), who conducted a qualitative case study, were less positive. Although the researchers reported a growth in prosocial involvement in African American and Latina girls who participated in weekly sports sessions and life skills sessions, they only provided a few examples of improvements in behavioral competencies (Bruening et al, 2009). Terry et al (2014) reported no positive findings on social skills either, as they found that behavioral problems in youth who participated in school-based boxing sessions did not decrease.…”
Section: Social Life Skillsmentioning
confidence: 95%
“…Por ejemplo, en investigaciones recientes, con el propósito de entender y transformar las barreras identificadas por las adolescentes con relación a la participación en AF, Enright y O'Sullivan (2010) verificaron que un currículo negociado conectando la EF a los contextos culturales de sus vidas facilitaba su participación. Bruening et al (2009) llevaron a cabo una investigación centrada en un programa que combinaba el deporte y la AF, habilidades para la vida, y la tutoría con la vista puesta en la promoción de estilos de vida saludables para las niñas preadolescentes. Los resultados mostraron que las niñas se vuelven más comprometidas cuando se les permite tomar decisiones.…”
Section: Discussionunclassified
“…En la investigación de los factores asociados a la participación en la AF, los métodos cuantitativos son más comunes que los cualitativos (Allender et al, 2006). Sin embargo, los resultados de diversas investigaciones que han aplicado diferentes procedimientos cualitativos y han explorado las perspectivas de los jóvenes acerca de su participación en la AF en diferentes contextos (Azzarito y Solomon, 2005;Bruening et al, 2009;Enright y O'Sullivan, 2010;Sinelnikov y Hastie, 2010, Wright et al, 2003, mostraron que el enfoque cualitativo proporciona formas particulares de entender los factores relacionados con la participación en la AF y que han sido escasamente relatados en la literatura. De hecho, los métodos cualitativos pueden ser útiles en la obtención de una visión más profunda, no sólo sobre los factores asociados con la AF, sino también sobre cómo estos cambian con el tiempo.…”
unclassified
“…At 12-month followup improvements were found on anxiety, behavioural inhibition and social-emotional competence for children in the intervention group. In a program for preadolescent girls that combined sport/physical activity and mentoring for healthy lifestyle choices the girls experienced an increased sense of self-responsibility, connections to the community and a sense of belonging, along with developing planning and leadership skills (Bruening, Dover & Clark, 2010). Incorporating leisure education within these programs would enable youth to see how everyday enjoyable activities could both help them feel better and could help part of living a healthy life.…”
Section: Making a Case For Leisure Education For Mental Health Promotmentioning
confidence: 99%